Instrumental cycle for bandura solo «The first notebook of travels» by Lyudmyla Fedorova-Kohanska: performance trend - Zadorozhna, Vita-Viktoria (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study is to research the instrumental cycle by L. Fedorova-Kohanska "The First Travel Notebook". Bandura, as a universal instrument, the technical level of which makes it possible to perform works of various styles and complexity, is gaining more and more popularity among listeners, allowing various creative ideas to be realized. Bandura repertoire is traditionally created not only by composers, but also bandura performers. Among such artists is Lyudmyla Fedorova-Kohanska, an outstanding Ukrainian bandura player, Honored Artist of Ukraine, head of the bandura department of the P. I. Tchaikovsky National Music Academy of Ukraine. The main objective of the study is to analyze the instrumental cycle of L. FedorovaKohanska "The First Travel Notebook" in the aspect of revealing the imaginative and technical potential of the work and the possibilities of its disclosure in performing interpretation. The methodology includes the complex of descriptive, genre-stylistic, comparative, performance analysis to identify structural features, technical and expressive properties of the cycle and its figurative and associative interpretation. Results and conclusions. The main socio-cultural and performance trends of modern Ukrainian bandura art are elaborated. The new role of the performer as a creator-composer has been defined. Powerful changes in public perception of bandura have been noted. The new technical capabilities of the tool are revealed with an emphasis on updating the sound production technique. The instrumental cycle "The First Travel Notebook" by Ludmyla Fedorova-Kohanska was analyzed in terms of sociocultural and performance trends. The program status of the cycle is revealed and the origin of all the program names of the parts of the "First Travel Notebook" is highlighted. The main compositional techniques used by the composer are characterized: technical (left hand overturning, interval and chord chains, broken arpeggios and movement with arranged consonances, rehearsals, technical passage structures) and sound imaging (articulation techniques, stroke elements, creation of timbre effects). The author’s executive interpretation of the cycle is presented. The features of the artist’s individual compositional style have been clarified.